Determining an optimal recovery time for construction rebar workers after working to exhaustion in a hot and humid environment - Chan, A.; Yi, Wen; Wong, D.; Yam, M.; Chan, D. (2012)
This paper is an extension to a paper previously published in the journal Building and Environment. Having determined an optimal recovery time in a controlled climatic environment, this paper aims to investigate the real impact on construction rebar workers by replicating the clinical experimentation to a series of field studies. Field studies were conducted during the summer time in Hong Kong. Nineteen rebar workers performed tasks of fixing and bending steel reinforcement bars on two building construction sites until voluntary exhaustion and were allowed to recover on site until their physiological conditions returned to the pre-work level or lower. Physiological Strain Index (PSI) was used as a yardstick to determine the rate of recovery. A total of 411 sets of meteorological and physiological data collected over fourteen working days between July and August of 2011 were collated to derive the optimal recovery time. It was found that on average a rebar worker could achieve 94% recovery in 40 min; 93% in 35 min; 92% in 30 min; 88% in 25 min; 84% in 20 min; 78% in 15 min; 68% in 10 min; and 58% in 5 min. Curve estimation results showed that recovery time is a significant variable to predict the rate of recovery (R 2 = 0.99, P < 0.05). Additional rest times should be introduced between works in extreme hot weather to enable workers to recover from heat stress. Frequency and duration of each rest time should be agreed among different stakeholders based on the cumulative recovery curve. © 2012 Elsevier Ltd.